(untitled) (Andamios, Revista de Investigación Social, 2025)
This essay elaborates on the organization built by the activist efforts of mad studies and pride as academic-political resistance to the impositions of power-knowledge imposed by psy dispositive. It is argued that this dispositive is an extension of the biomedical and neoliberal model that regulates identities and behaviors, with stigmatizing and excluding effects in the constitution of the “sane” subject. The essay also presents a dissertation on the relationship between discourse and affect, as a couple that can help find escape routes to the imposed cannons of the psy dispositive, the biomedical model of mental health and the subjectivation mechanisms it allows